Analysis of the Company's Cash Flow Statement Kopinian Café - Aisyah Nurul Aini; Betty Subartini; Muhammad Iqbal Al-Banna Ismail (Research Collaboration Community (RCC), 2022)
Café is a very popular place for young people today, so many entrepreneurs open up opportunities in this business, but seeing a promising market, entrepreneurs still find it difficult to manage their financial reports. Financial reports are important for a company to know the financial condition of the business being run, and the preparation of non-detailed financial statements will also have a big impact on the company, which causes difficulties in developing a business and including investment capital. With the existence of financial reports on. This writing aims to help the company